Tinjauan Viktimologi Tindak Pemerkosaan oleh Ayah terhadap Anak Kandung di Kota Kupang - Andini Raehun Putri Sidin; Heryanto Amalo; Rudepel Petrus Leo (Pusat Riset dan Inovasi Nasional, 2025)
Kupang City is the capital of East Nusa Tenggara province which is inseparable from the case of rape of a father against a biological child. There are several cases including a minor being a victim of sexual violence. Tragically, a student of a junior high school in Kupang became a victim of rape committed by her biological father. The case of adultery committed by the father to his biological child was handled by the PPA Unit of the Kupang City Police Satreskrim in 2019. The results of this study show that (1) the causative factor for children as victims of rape by biological fathers in Kupang City is the influence of lack of religious understanding in the family environment that causes the perpetrator to commit crimes. The actions carried out by the perpetrator were carried out repeatedly without thinking about the mental and physical influence of the victim. For this reason, it is hoped that religious understanding can be applied in the family environment so that it becomes a moral benchmark for one's life as well as the cases researched by the author. (2)) The impact on children as victims of rape by biological fathers in Kupang City is the physical and social impact experienced by the victim after the incident that befell the victim. (3) Legal Protection Efforts for Children as Victims of Rape by Biological Fathers in Kupang City In particular, Indonesia has its own law regarding the protection of children, namely Law Number 23 of 2004 concerning Child Protection. In Articles 81 and 82 of the Law on Child Protection, it is stipulated that the perpetrator of sexual abuse of children is sentenced to a maximum of 15 years in prison.